Coral larvae spreading based on oceanographic condition in Biawak Islands, West Java, Indonesia - CANDRA A. FITRIADI; YAYAT DHAHIYAT; NOIR P. PURBA; SYAWALUDIN A. HARAHAP; DONNY J. PRIHADI (Biodiversitas Journal of Biological Diversity, 2017)
Fitriadi CA, Dhahiyat Y, Purba NP, Harahap SA, Prihadi DJ. 2017. Coral larvae recruitment based on oceanography condition in Biawak Islands, West Java, Indonesia. Biodiversitas 18: 681-688. This research aimed to know the recruitment pattern of planula in the Biawak Island. The dispersion of planula and corals recruitment as an important factor to determine the distribution of the adult corals. The spawning and brooding are the beginning processes of planula dispersion. Dispersion factors are highly influenced by water environment factors. The main factor in planula dispersion is sea currents, wind, tide, and bathymetry. The circulation of sea currents on Biawak Islands waters is influenced by the tidal movement. The results of research showed that Biawak Islands waters have mixed tide prevailing semidiurnal type of tidal movement. Currents of Biawak Islands waters moved from the northern toward the southern with a range of speed between 0.045-0.075 m/s on northeast and south and for west and north range of speed of sea currents are between 0.015-0.195 m/s, the sea currents movement of Biawak Islands waters was dominated by tidal movement. Biawak Islands have varying wind speed, the most direction of wind moved to northwestern toward southeastern by predominance speed 4.8-7.2 m/s. The results of research showed that planula on the Biawak Island moved to northern and northeastern at high tide and then moved to southern and southeastern at a low ebb with the furthest movement of planula on the Biawak Island was 2.2 km. The furthest movement of planula on the Gosong Island was 1.66 km and planula dispersed to the east and west region of Gosong Island, on the Cendikia Island planula dispersed to northern and eastern with the furthest movement of planula on the Cendikia Island was 0.44 km. Based on the movement of planula can be concluded that source of coral reefs on the Gosong Island derived from the coral reefs on the Biawak Island.